EVALUATION OF NEW LETTUCES CULTIVARS PRODUCED IN DIFFERENT CROP SYSTEMS - Abe Rossi, Claudia Margareth; Fontana, Larissa; Zanni Hubinger, Silviane; Vicentini-Polette, Carolina Medeiros; Ferreira, Marcos David; Fillet Spoto, Marta Helena; Sala, Fernando Cesar; Verruma-Bernardi, Marta Regina (REVISTA DE AGRICULTURA, 2020)
Romanela and Rubinela lettuce cultivars are innovative varieties, since they are crunchy and tropicalized. This study aimed to verify characteristics and quality of these cultivars produced in conventional, hydroponic and organic systems. The lettuces were evaluated regarding leaf area, leaf size, unit leaf area, fresh mass, mass loss, turgidity pressure, instrumental color, pH, total soluble solids, total titrable acidity, total phenolic compounds, and sensory characterization. The cultivation systems influenced the physical characteristics size, weight and mass loss of Romanela lettuce, and fresh mass and mass loss for Rubinela lettuce. In the sensory evaluation, there were significant differences for green color, leaf size, crunchiness, grassy aroma and sweet taste for Romanela cultivar, the conventional and hydroponic being preferred. For Rubinela cultivar, there were differences for purple and green colors, leaf thickness and size, sweet and bitter tastes, the conventional and hydroponic being preferred, and the hydroponic presenting the highest purchase intention.